Development of Electronic Handout Media Using the Double Loop Problem Solving (DLPS) Model on Physics Material For Class X High School Student - Miranda Agustina; Yuberti Yuberti; Muhammad Ridho Syarlisjiswan (Jurnal Pembelajaran Fisika, 2023)
This study aims to develop electronic handout media with the Double Loop Problem Solving (DLPS) model on physical materials, namely energy source materials for tenth-grade high school students to determine the feasibility and attractiveness of the electronic handout being developed. This electronic handout was created using Smart Apps Creator which is a mobile application for Android and iOS without a programming code and the form is html.5 and exe. This study uses the ADDIE model which consists of five stages, namely analysis, design, development, implementation, and evaluation. This research was conducted in two Bandar Lampung tenth-grade schools and was validated by material and media experts. This study aims to get a validation score of 83% in the